Basal and inducible Osterix expression reflect equine mesenchymal progenitor cell osteogenic capacity - Andrietti, Antonella Liza Pantaleoni; Durgam, Sushmitha S.; Naumann, Brittany; Stewart, Matthew (Frontiers in Veterinary Science, 2023)
Introduction Mesenchymal stem cells are characterized by their capacities for extensive proliferation through multiple passages and, classically, tri-lineage differentiation along osteogenic, chondrogenic and adipogenic lineages. This study was carried out to compare osteogenesis in equine bone marrow-, synovium- and adipose-derived cells, and to determine whether osteogenic capacity is reflected in the basal expression of the critical osteogenic transcription factors Runx2 and Osterix. Methods Bone marrow, synovium and adipose tissue was collected from six healthy 2-year-old horses. Cells were isolated from these sources and expanded through two passages. Basal expression of Runx2 and Osterix was assessed in undifferentiated third passage cells, along with their response to osteogenic culture conditions. Results Bone marrow-derived cells had significantly higher basal expression of Osterix, but not Runx2. In osteogenic medium, bone-marrow cells rapidly developed dense, multicellular aggregates that stained strongly for mineral and alkaline phosphatase activity. Synovial and adipose cell cultures showed far less matrix mineralization. Bone marrow cells significantly up-regulated alkaline phosphatase mRNA expression and enzymatic activity at 7 and 14 days. Alkaline phosphatase expression and activity were increased in adipose cultures after 14 days, although these values were less than in bone marrow cultures. There was no change in alkaline phosphatase in synovial cultures. In osteogenic medium, bone marrow cultures increased both Runx2 and Osterix mRNA expression significantly at 7 and 14 days. Expression of both transcription factors did not change in synovial or adipose cultures. Discussion These results demonstrate that basal Osterix expression differs significantly in progenitor cells derived from different tissue sources and reflects the osteogenic potential of the cell populations.